Lipopolysaccharide induces a fibrotic‐like phenotype in endothelial cells. Issue 6 (2nd May 2013) - Echeverría, César; Montorfano, Ignacio; Sarmiento, Daniela; Becerra, Alvaro; Nuñez‐Villena, Felipe; Figueroa, Xavier F.; Cabello‐Verrugio, Claudio; Elorza, Alvaro A.; Riedel, Claudia; Simon, Felipe
Abstract Endothelial dysfunction is crucial in endotoxaemia‐derived sepsis syndrome pathogenesis. It is well accepted that lipopolysaccharide (LPS) induces endothelial dysfunction through immune system activation. However, LPS can also directly generate actions in endothelial cells (ECs) in the absence of participation by immune cells. Although interactions between LPS and ECs evoke endothelial death, a significant portion of ECs are resistant to LPS challenge. However, the mechanism that confers endothelial resistance to LPS is not known. LPS‐resistant ECs exhibit a fibroblast‐like morphology, suggesting that these ECs enter a fibrotic programme in response to LPS. Thus, our aim was to investigate whether LPS is able to induce endothelial fibrosis in the absence of immune cells and explore the underlying mechanism. Using primary cultures of ECs and culturing intact blood vessels, we demonstrated that LPS is a crucial factor to induce endothelial fibrosis. We demonstrated that LPS was able and sufficient to promote endothelial fibrosis, in the absence of immune cells through an activin receptor–like kinase 5 (ALK5) activity–dependent mechanism. LPS‐challenged ECs showed an up‐regulation of both fibroblast‐specific protein expression and extracellular matrix proteins secretion, as well as a down‐regulation of endothelial markers. These results demonstrate that LPS is a crucial factor in inducing endothelial fibrosis in the absence of immune cells through an ALK5‐dependent mechanism. It is noteworthy that LPS‐induced endothelial fibrosis perpetuates endothelial dysfunction as a maladaptive process rather than a survival mechanism for protection against LPS. These findings are useful in improving current treatment against endotoxaemia‐derived sepsis syndrome and other inflammatory diseases.